IMPACT OF INORGANIC AND ORGANIC SOURCES OF NITROGEN AND ROW SPACING ON BABY CORN Y CORN (Zea mays L.) - BARMA JNANA NAGA SRI RAMYA,; SHIKHA SINGH,; P. VASU DEVA REDDY,; NARREDDY HINDUJA, (The Bioscan, 2021)
A field experiment was conducted during Zaid 2020 at Crop Research Farm, Department of Agronomy, SHUATS, Prayagraj (U.P). The treatment consisted of 75% Nitrogen through urea + 25% Nitrogen through FYM + 30 x 15 cm whose effect is observed on Baby corn. Experiment was laid out in RBD there were 9 treatments and replicated thrice it was observed that T5 75% Nitrogen through urea + 25% Nitrogen through FYM + 30 x 15 cm was found to be the best treatment for obtaining growth and yield attributes such as plant height (191.39 cm), number of leaves (12.23 cm ), plant dry weight (91.98 g/plant) and fodder yield (36.66 t/ha) while net return (125793 Rs/ha) and B:C ratio (1.84) were also recorded in 75% Nitrogen through urea + 25% Nitrogen through FYM + 30 x 15 cm. From the above investigation it was concluded that application of 75 % Nitrogen through urea + 25% Nitrogen through FYM + 30 x 15 cm was more productive as well as economic.